Recovery of singularities in a fourth-order operator on the line from limited data. (3rd May 2016) - Tyni, Teemu; Harju, Markus; Serov, Valery
Abstract: We consider a differential operator of order four with three coefficients which may be complex valued. We prove that the Born approximation can be used efficiently to recover essential information about a combination of the coefficients from the knowledge of the reflection coefficient. Numerical examples illustrate the feasibility of this method.